2019
DOI: 10.3390/electronics8070812
|View full text |Cite
|
Sign up to set email alerts
|

Unobtrusive Sleep Monitoring Using Movement Activity by Video Analysis

Abstract: Sleep healthcare at home is a new research topic that needs to develop new sensors, hardware and algorithms with the consideration of convenience, portability and accuracy. Monitoring sleep behaviors by visual sensors represents one new unobtrusive approach to facilitating sleep monitoring and benefits sleep quality. The challenge of video surveillance for sleep behavior analysis is that we have to tackle bad image illumination issue and large pose variations during sleeping. This paper proposes a robust metho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(11 citation statements)
references
References 43 publications
0
9
0
Order By: Relevance
“…Visual context (e.g., keep track of daily living activities performed by the older adult, locating the older adults in house) [43][44][45][46] Acoustic sensors Fall-detection [48][49][50] Ambient sensors (temperature, appliances, toilet)…”
Section: Touch Sensorsmentioning
confidence: 99%
See 1 more Smart Citation
“…Visual context (e.g., keep track of daily living activities performed by the older adult, locating the older adults in house) [43][44][45][46] Acoustic sensors Fall-detection [48][49][50] Ambient sensors (temperature, appliances, toilet)…”
Section: Touch Sensorsmentioning
confidence: 99%
“…Piezoelectric film sensors can be embedded in the bed mattress to monitor the sleep quality, based on the variation of the heart and respiration rate and the binary actigram [42]. Microsoft Kinect camera can be employed to detect the human shape and the body movements and a sensor tag that provides information about the sleep environment such as the temperature and humidity [43], while Near-Infrared camera can be used to analyze the sleep behavior, based on the collected videos/images [44].…”
Section: Touch Sensorsmentioning
confidence: 99%
“…Two of the papers aimed at the detection of the presence of a human being at specific locations either using pre-placed sensors [2], or using Bluetooth signals (assuming that the person being monitored carries a Bluetooth device) [8]. The remaining three papers aimed at direct human activity detection using inertial sensors [9], time of flight sensors [9], near-infrared camera [10], and Microsoft Kinect sensor [11].…”
Section: Smart Healthcare Systemsmentioning
confidence: 99%
“…In [10], Wang et al reported a non-intrusive video-based sleep monitoring system. They addressed some major technical challenges in detecting human sleep poses with infrared images.…”
Section: Smart Healthcare Systemsmentioning
confidence: 99%
“…In general, the use of image and depth sensors [1,7,[9][10][11][12] allow sleep monitoring and 3D modeling of the chest and abdomen volume changes during breaths as an alternative to conventional spirometry with the use of red-green-blue (RGB) cameras [13,14], infrared cameras [15,16], or Doppler multi-radar systems [17] in addition to ultrasonic and biomotion sensors [18][19][20][21]. The paper provides motivation for further studies of methods related to big data processing problems, dimensionality reduction, principal component analysis, and parallel signal processing to increase the speed, accuracy, and reliability of the results.…”
Section: Introductionmentioning
confidence: 99%